2022
DOI: 10.22541/au.166733705.50712709/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Upregulation of proBDNF/p75NTR signaling in lymphocytes and its correlation with inflammatory markers in patients with major depression

Abstract: Major depressive disorder (MDD) is a serious mental disorder with unclear pathogenesis. ProBDNF is the precursor protein of brain derived neurotrophic factor (BDNF) expressed in the central nervous system and peripheral tissues. Previous studies showed that the blood levels of both proBDNF and inflammatory cytokines in MDD were increased, but which blood cell types express proBDNF and its receptors is not known. Furthermore, the relationship between proBDNF/p75NTR and inflammatory cytokines in peripheral blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Latest research by Yang et al has revealed that in patients with Major Depressive Disorder (MDD), there is an elevation in the expression of proBDNF and its receptors in peripheral blood mononuclear cells. This is associated with inflammatory markers, suggesting a potential link between proBDNF/p75NTR signaling and NF-κB activation [157]. This modulates subsequently the expression of inflammatory factors and related apoptotic proteins PSD95, synaptophysin (SNP) and P-cofilin or inhibits the expression of anti-apoptotic proteins like RIP2, cleaved caspase-3 and cytochrome C to promote PSD.…”
Section: Brain-derived Neurotrophic Factormentioning
confidence: 99%
“…Latest research by Yang et al has revealed that in patients with Major Depressive Disorder (MDD), there is an elevation in the expression of proBDNF and its receptors in peripheral blood mononuclear cells. This is associated with inflammatory markers, suggesting a potential link between proBDNF/p75NTR signaling and NF-κB activation [157]. This modulates subsequently the expression of inflammatory factors and related apoptotic proteins PSD95, synaptophysin (SNP) and P-cofilin or inhibits the expression of anti-apoptotic proteins like RIP2, cleaved caspase-3 and cytochrome C to promote PSD.…”
Section: Brain-derived Neurotrophic Factormentioning
confidence: 99%